A Brief Survey on Smart Grid Data Analysis in the Cloud. (2015) - Bereş, Adela; Genge, Béla; Kiss, Istvan
Abstract: Cloud Computing has become more and more of a choice for storing and processing data due to the performance, scalability, availability and interoperability that it offers. The adoption of generic off-the-shelf Information and Communication Technologies (ICT) for the Smart Grid has come with many advantages, but also raised issues regarding the security, availability and reliability of the Smart Grid. The data generated by the Smart Grid's systems has the properties of a time series and its analysis needs to be secure and in real-time. As shown in this paper, cloud computing has become a real candidate for Smart Grid data analysis. We present the particularities of the data generated in the Smart Grid and the operations involved in its analysis. As well we compare existing solutions for stream data processing against this basic set of operations.